The Filipino broadcasters on overseas propaganda radio in World War II - Enriquez, Elizabeth L. (2013)
The use of radio broadcasting for propaganda in the Second World War is well known. In the Philippines, the pre-war KZRH was taken over by the invading Japanese forces, who change its call letters to PIAM and used it to try to win the hearts and minds of Filipinos. Counter-propaganda was heard on the shortwave signals emanating from the US and other countries.
Also recorded in historical accounts is the work of some Filipinos who broadcast on PIAM, Voice of Freedom and Voice of Juan dela Cruz. Little is known, however, about the work of Filipinos in overseas propaganda radio stations, such as that of Carmen Ligaya on KGEI in San Francisco, California, who was the US's answer to Tokyo Rose; of at least seventeen others who was also broadcast on KGEI; and of Norman Reyes on the Zero Hour Radio Tokyo. Their experiences, previously under-examined, indicate the extent by which radio broadcasting has since been a tool for shaping public consciousness, particularly in wartime.
Keywords: Radio in propaganda; World War II -- Radio broadcasting and the war; Radio broadcasters; World War II propaganda